Study on Edmodo Application to Improve Teaching Reading Skill at the First Grade of SMKN 01 Kamal - Nova Masluha; Moh. Arief Wahyudi; Moh. Hafidz (Penerbit STKIP PGRI Bangkalan, 2021)
Reading is one method of the basic learning in English skill that should be mastered by student in English. This research have been conducted in March 2020 at SMKN 01 Kamal. The researcher was expected how far student can write especially in narrative text. The researcher has found that some student bored and still difficulties in reading. This research in order to know are the use students reading skill and respond in student reading skill in narrative text. Researcher is used edmodo application in blended learning of the students reading skill in narrative text. The researcher uses data fieldnote and student interview. In this study was conducted three meeting in observation. The result of teaching learning process in the classroom can be success if almost some students can make retell of the narrative text by using blended learning in edmodo application and only a small percentage of the research in students who are still having trouble to understanding retell or the narrative text by using blended learning method. In this case, most of the students could reach the criteria of the success and suitable in the uses of the researcher as a strategy in teaching and learning in the classroom.